Positive Face Threatening Acts Analysis in “Purple Hearts” Movie - Nangin, Faith Courtney; Andries, Fivy; Lolowang, Imelda (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This research aims to investigate the Positive Face-Threatening Acts (FTAs) in the movie Purple Hearts (2022), focusing on how they were directed toward the main character, Cassie. The study is qualitative, presenting findings in descriptive analysis. The data consists of key dialogues from the movie, which were transcribed and analyzed using Brown and Levinson’s (1987) politeness theory. This research examinied how Cassie’s autonomy and social identity are challenged throughout the film. The results indicate that Cassie frequently experiences disapproval, criticism, contradictions, and restrictions on her independence. The findings show that among the positive FTAs, there were 1 instances of disagreement, 6 of criticism, 4 of contradiction, 3 of dismissal, 5 of accusation, 2 of complaints, and 1 of face-saving. These FTAs shape her character dynamics, highlighting conflicts, power struggles, and emotional tension in the narrative. This research contributes to the understanding of pragmatics in cinematic discourse and provides insights into how language reflects interpersonal relationships in film.